Heterogeneity in Alcohol-Related Severity and Interests in Going to Treatment in Community Adults with Alcohol Use Disorder (AUD). (24th August 2022) - Maisto, Stephen A.; Aldalur, Aileen; Abar, Beau; Stecker, Tracy; Chiang, Andrew; Conner, Kenneth
Abstract: Rationale: Alcohol use disorder (AUD) is highly prevalent among adults in the US and is associated with substantial personal and societal costs. Yet only a small percentage of adults with AUD initiate treatment, including those with severe AUD symptoms who are most in need of treatment. In this paper we use latent profile analysis (LPA) to describe differences in symptoms of AUD severity and alcohol-related consequences among untreated adults with severe AUD symptoms who were recruited from the community. Identification of such differences will result in better understanding of this population and will improve methods of treatment outreach. Method: The LPAs were conducted on the baseline data of 403 (50% male, 77% White, M age = 40.74 with severe AUD recruited from the community and enrolled in a trial of an intervention designed to encourage treatment initiation. Participants reported no prior AUD treatment history. The LPAs were based on indicators of AUD severity, alcohol-related negative consequences, and self-reported intention to initiate AUD treatment. Results: The LPAs revealed 4 profiles. Profile membership was predicted by baseline participant sex and whether they were living with a partner and was associated with baseline past 30-days alcohol consumption. Conclusions: The findings characterize and describe the variability among adults in the community with untreated severe AUD on variables that tend to motivate such individuals to seek treatment, which could significantly advance treatment outreach efforts.